Originalism, federalism, and the American constitutional enterprise : a historical inquiry - Purcell, Edward A. (New Haven : Yale University Press, 2007)
In this lively historical examination of American federalism, a leading scholar in the field refutes the widely accepted notion that the founding fathers carefully crafted a constitutional balance of power between the states and the federal government. Edward A. Purcell Jr. bases his argument on close analysis of the Constitution's original structure and the ways that structure both induced and accommodated changes over the centuries. There was no clear agreement among the founding fathers regarding the "true" nature of American federalism, Purcell contends, nor was there a consensus on "correct" lines dividing state and national authority. Furthermore, even had there been some true "original" understanding, the elastic and dynamic nature of the constitutional structure would have made it impossible for subsequent generations to maintain any "original" or permanent balance. The author traces the evolution of federalism through the centuries, focusing particularly on shifting interpretations founded on political interests. He concludes with insights into current issues of federal power and a discussion of the grounds on which legitimate decisions about federal and state power should rest.
Introduction. The inquiry. -- American constitutional federalism as a normative problem -- pt. I. Structural intrinsics. -- Federalism as doubly blurred -- Federalism as fractionated -- Federalism as instrumental -- Federalism as contingent -- pt. II. Consequential dynamics. -- Kaleidoscopic politics -- Readjusting components -- Contested authorities -- Evolving understandings -- pt. III. Conclusion. -- The "arduous enterprise."
Includes bibliographical references (pages 207-292) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Federal government -- United States; Constitutional history -- United States; United States -- Politics and government; Histoire constitutionnelle -- États-Unis.; États-Unis -- Politique et gouvernement; BUSINESS & ECONOMICS / General; Constitutional history; Federal government; Politics and government; United States